Upaya Peningkatan Administrasi Publik terhadap Kepuasan Masyarakat Dalam Pengurusan E-KTP di Kantor Dinas Kependudukan dan Pencatatan Sipil Aceh Tenggara - Dina Tahfiza; Mustafa Kamal Rokan (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study found that amid numerous issues within the service of e-ID, the Department of Population and Civil Registration Kabupaten Aceh Tenggara tried to create a spread of methods to extend His ministry. The strategy is to develop a structure through best management of the division of labor, collaboration with districts and extra manpower. Development of procedures through the simplification requirements, proactive service and distribution of e-ID cards are printed. Infrastructure development is completed with the addition of printing instrumentality and repair facilities in the District of different services. On the cultural development work, has been finished coaching and extra hours of service. Keyword: Strategy, Public Services, e-ID card